2009
DOI: 10.1590/s0066-782x2009001200016
|View full text |Cite
|
Sign up to set email alerts
|

Pressão Arterial em jovens como marcador de risco cardiovascular. Estudo do Rio de Janeiro

Abstract: Background: The study of the cardiovascular risk variables in young populations is fundamental to establish primary prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
(75 reference statements)
2
10
0
6
Order By: Relevance
“…Corroborating the literature 2,8-14,29 , the present cohort showed higher prevalence of mean insulin and insulin resistance as assessed by HOMA-IR in early adulthood in GH individuals, thus reflecting a more unfavorable metabolic profile in this population. This group also had higher serum leptin levels in comparison to GN and lower mean adiponectin than GN, although the latter without a statistically significant difference.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Corroborating the literature 2,8-14,29 , the present cohort showed higher prevalence of mean insulin and insulin resistance as assessed by HOMA-IR in early adulthood in GH individuals, thus reflecting a more unfavorable metabolic profile in this population. This group also had higher serum leptin levels in comparison to GN and lower mean adiponectin than GN, although the latter without a statistically significant difference.…”
Section: Discussionsupporting
confidence: 82%
“…In the Muscatine study 23 , the authors demonstrated that more than half of the hypertensive children were also obese. In our country, several publications, especially those of the RJS cohort, had already suggested the importance of body composition in the determinism of BP in children and adolescents 8-14,24,25 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The present study is part of the Rio de Janeiro study (ERJ) [13][14][15] , a longitudinal line of research on blood pressure (BP) and other cardiovascular RF in children and adolescents and their families, which has been developed since 1983 and aims to evaluate the association between PWV and BP, anthropometric and metabolic variables, including adipocytokines, in young adults.…”
Section: Introductionmentioning
confidence: 99%